When to Sow Your Seed for Optimal Forest Rehabilitation ⎯ Lessons from the Jarrah Forest of South Western Australia - Worthington, T; Braimbridge, MF; Vlahos, S (Mine Closure 2006: First International Seminar on Mine Closure, 2006)
As mining is a temporary land use (EPA, 1995), there is a need for the disturbed land to be rehabilitated in accordance with long term land use goals. In Australia, the objective of many post-mining rehabilitation programmes is to establish a native ecosystem similar to that of surrounding undisturbed sites (Bell, 2001). Successfully established native ecosystems have the advantage of being self-sustaining and resilient to disturbance, whilst supporting native fauna and requiring minimal long-term management inputs. In Western Australia, the establishment of a native ecosystem following bauxite mining is typically achieved through topsoil return, broadcast seeding and planting of green stock as required (Roche et al., 1997; Vlahos et al., 1999). Direct seeding has been found to be the least costly way to establish native species and is necessary to supplement the seed bank stored in the returned topsoil (De Villiers et al., 2003; Koch and Ward, 1994; Turner, 2006; Ward et al., 1996). Typically, the composition of the applied seed mix reflects the desired species diversity of the mature rehabilitation and is based on estimated germination and establishment rates. There is evidence to suggest that the floristic composition of rehabilitated bauxite mines in the south-west of Western Australia can reflect the initial vegetation complex, even many years after seeding (Grant and Loneragan, 2001; Koch and Ward, 1994; Norman et al., 2006). This, combined with the high cost of rehabilitation, makes it preferable to optimise the establishment of the desired plant community early in the rehabilitation process. However, ecosystem restoration is a complex process and there are many barriers to successful seedling emergence and establishment, including seed viability, ambient temperature, soil moisture, light, predation and competition effects (Beardsell and Richards, 1987; Majer et al., 1984; van der Valk and Pederson, 1989). Within the mining industry, the time of year that sowing occurs has been identified as a factor with the potential to impact on the abundance of emerged plants in newly established rehabilitation areas (Turner, 2006; Ward et al., 1996). Where broadcast seeding is used to assist in the regeneration of plants on mined sites, sowing at an appropriate time can be a low cost way to maximise plant establishment (Brofas and Karetsos, 2002; Turner, 2006). In south-western Australia, germination usually occurs in late autumn and winter (Grant and Koch, 1997), and sowing in May has been found to result in greater seedling emergence than sowing in winter (July) (Turner, 2006). In this paper, we present the findings of a research trial based at a bauxite mine in the south-west of Western Australia, which attempted to quantify the effect of different sowing times on seedling emergence and establishment. Seed was sown at three different times: mid dry season, late dry season and at the break of season. It was hypothesised that the early sowing would result in the poorest seedling emergence and establishment, as the seed would be exposed on the soil surface for many months before the break of season and consequently vulnerable to desiccation, predation and dispersal. Mine Closure 2006 ― Andy Fourie and Mark Tibbett (eds) © 2006 Australian Centre for Geomechanics, Perth, ISBN 0-9756756-6-4 Mine Closure 2006, Perth, Australia 319